Increasing planting density can improve the yield of Tartary buckwheat - Zhou, Qiuyue; He, Peiyun; Tang, Jingang; Huang, Kaifeng; Huang, Xiaoyan (Frontiers in Plant Science, 2023)
Planting densities and nitrogen fertilizer application rates determine the yield of crops. Tartary buckwheat is a pseudocereal crop with great health care and development values. However, little is known about application of nitrogen fertilizer and planting density on the physiological characteristics of Tartary buckwheat. This study aims to clarify the effect of planting density on the senescence and yield of Tartary buckwheat under low nitrogen conditions. A 2-year field experiment was conducted on Tartary buckwheat (Jinqiao 2) to study the effects of different planting densities (8 × 105, 10 × 105, 12 × 105, 14 × 105, and 16 × 105 plants·ha−1) on the root morphology and activity, chlorophyll and malondialdehyde (MDA) contents, antioxidant enzyme activity, photosynthetic characteristics, agronomic traits, and yield of Tartary buckwheat in the absence of nitrogen fertilizer treatment. With the increase in planting density, the root morphological indices and activities; chlorophyll a, chlorophyll b, and carotenoid contents; superoxide dismutase and peroxidase activities; net photosynthetic rate; transpiration rate; intercellular CO2 concentration and transpiration rate; main stem node, branch, and leaf numbers; grain number and weight per plant; and 1000-grain weight of Jinqiao 2 decreased continuously, whereas plant height and leaf MDA content increased continuously. The yield of Tartary buckwheat first increased and then decreased with the increase in planting density. The yield under 14 × 105 plants·ha−1 treatment increased by 68.61%, 44.82%, 11.00%, and 22.36%, respectively, relative to that under 8 × 105, 10 × 105, 12 × 105, and 16 × 105 plants·ha−1treatments. In summary, planting at an appropriately high density (14 × 105 plants·ha−1) can promote the increase in the yield of Tartary buckwheat populations under low nitrogen conditions and is recommended for use in production to achieve the high-yielding and nitrogen saving cultivation of Tartary buckwheat. This research can serve as a theoretical basis to jointly achieve the high yield and nitrogen saving of Tartary buckwheat.